Traces of History, Spirituality, and Architecture: A Study of Surau Cerobong, Padang, West Sumatra - Nurfalina, Yuliana; Darmawan, Budi; Alhuzaini, Muhammad; Hasibuan, Nur Anisah; Anggraini, Riri (Journal of Philology and Historical Review, 2023)
This research is a scientific article carried out in the field with the aim of studying the relationship between society and the Surau Cerobong (surau can be referred to as a small mosque), from historical and archaeological views. This study covers the history, social and religious activities carried out at Surau Cerobong, and the shape of the building. This research uses historical research methods as the main method and is reinforced by archaeological research methods. The historical method is used through the steps of heuristics, source criticism, synthesis, and historiography. While the archaeological method is used to analyze the physical building of the surau. The results of this study found that Surau Cerobong was built on the initiative of Imam Karim in 1941, as a place to develop Islamic teachings. Aside from being a place to perform the obligatory prayers, the surau is also used as a place to teach tariqah and conduct suluk. In architectural aspects, there are parts that have similarities with the Persian architectural style during the Seljuk Dynasty.